FEATURES OF THE TRANSMISSION OF NEW WORDS IN UZBEKISTAN DICTIONARIES AND ISSUES OF THEIR TEACHING - Maxmudova Yulduz Odil kizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the lexical updates taking place in the modern Uzbek language, the principles of reflecting new words in dictionaries, and the issues of teaching them in the educational process. Neologisms arising as a result of language development are evaluated as a manifestation of political, economic, cultural and technological changes in the life of society in the language system. During the research, the features of recording new words in explanatory dictionaries and electronic dictionaries of the Uzbek language were studied. Also, the linguodidactic aspects of teaching neologisms in native language classes were covered. The results of the study showed that the inclusion of new words in dictionaries and their implementation in the educational process is an important factor in language development and the development of students' lexical competence.